Endoscopic endodontic microsurgery: 2-year evaluation of healing and functionality - Silvio Taschieri; Massimo Del Fabbro (Sociedade Brasileira de Pesquisa Odontológica, 2009)
This prospective clinical study aimed to evaluate the benefits of the endoscope as an aid to root-end management, and to assess the treatment outcome during 2 years following surgery. Forty-three endodontic surgical procedures in 30 patients were performed with the aid of an endoscope and followed for a period of 2 years. Radiographic criteria and clinical evaluation were used to assess the outcome. All cases were evaluated in terms of healing and functionality. 91.1% and 90.7% of the teeth evaluated after 1 and 2 years, respectively, were classified as successful. We found no statistically significant differences for both healing and functionality between the 1- and 2-year evaluations. No difference related to tooth type or tooth location was found at the 2-year follow-up. Fisher's exact test was used to statistically assess the difference between successful and unsuccessful cases for each of the variables considered. The endoscope can be an aid for endodontic surgical procedures in terms of both periapical healing and functionality up to 2 years follow-up.